2013
DOI: 10.1111/ctr.12219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor and recipient age difference on long‐term allograft survival after living donor renal transplantation: analysis of 478 cases

Abstract: Only the age difference between donor and recipient exerts an adverse impact on graft outcome after living donor renal transplantation, whereas donor age, recipient age, donor/recipient gender, and ABO incompatibility do not significantly influence renal allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…The possibility that older recipient age per se may confound the results of studies examining outcomes associated with donor age led to the emergence of donor/recipient age difference as more robust predictor of allograft outcomes. [21][22][23] In keeping with these reports, our study has shown that increasing donor/recipient age difference is associated with poorer long-term graft survival, with an approximately 10% increase in graft loss for every 10-year increase in donor/recipient age difference. At the other end of the continuum of donor/recipient age difference, studies have also shown good outcomes for pediatric patients who received DD kidneys from donors younger than their recipients.…”
Section: Discussionsupporting
confidence: 88%
“…The possibility that older recipient age per se may confound the results of studies examining outcomes associated with donor age led to the emergence of donor/recipient age difference as more robust predictor of allograft outcomes. [21][22][23] In keeping with these reports, our study has shown that increasing donor/recipient age difference is associated with poorer long-term graft survival, with an approximately 10% increase in graft loss for every 10-year increase in donor/recipient age difference. At the other end of the continuum of donor/recipient age difference, studies have also shown good outcomes for pediatric patients who received DD kidneys from donors younger than their recipients.…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, only 2.6% of the transplantations were performed in older people. Although older age has been identified as a risk factor for graft loss in this and other studies (26,37,40) , some authors have questioned this assumption and have reported that the survival rates of patients aged <50 years were similar to those of patients aged >50 years (12,41). As a result, we believe age should not necessarily be a discriminatory factor against receiving a transplant.…”
Section: Discussionmentioning
confidence: 50%
“…34 Finally, we found that BK virus urinary infection could be a risk factor for SII development, beyond being an established factor for early graft loss. 35,36 Two of our patients with SII had an ongoing BK virus infection at the time of SII diagnosis. The total number of patients with BK virus infection in our renal transplant recipients, among more than 2000 kidney transplant procedures, 37 was 5.…”
Section: Discussionmentioning
confidence: 99%